Hydrogel for motion monitoring and / or drug delivery and preparation method and application thereof

By constructing a dual network hydrogel, using reversible dynamic chemical bonds and metal ion coordination bonds, the flexibility and biocompatibility problems of traditional conductive materials in motion monitoring and drug delivery are solved, achieving high sensitivity, degradability and Self-healing hydrogel material.

CN119490674APending Publication Date: 2025-02-21BEIHUA UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411652474.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Traditional conductive materials have problems such as poor flexibility, poor fit, and low biocompatibility in motion monitoring and drug delivery applications, and it is difficult to meet the needs of high sensitivity, degradability and self-healing.

Method used

Using a dual network hydrogel, a hydrogel with excellent mechanical properties is constructed by introducing reversible dynamic chemical bonds and metal ion coordination bonds. The hydrogel consists of N-hydroxyethylacrylamide-β-(acryloyloxy)propionic acid copolymer and carboxylated cellulose nanofibers, and zirconium ions are used as crosslinking agents and photoinitiators to enhance their performance.

Benefits of technology

It achieves high tensile ratio, excellent mechanical strength and toughness, can effectively monitor human movement and achieve long-term percutaneous drug delivery, and has self-healing and high biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141317580000051
    Figure BDA0005141317580000051
  • Figure BDA0005141317580000061
    Figure BDA0005141317580000061
  • Figure HDA0005141317590000011
    Figure HDA0005141317590000011
Patent Text Reader

Abstract

The invention relates to hydrogel for motion monitoring and / or drug delivery as well as a preparation method and application thereof, and relates to the technical field of new materials. The hydrogel is double-network hydrogel, and the double-network hydrogel comprises a first network, a second network and a cross-linking agent, the first network is mainly constructed from an N-hydroxyethyl acrylamide-beta-(acryloyloxy) propionic acid copolymer, the second network is mainly constructed from carboxylated cellulose nanofibers, and the cross-linking agent comprises zirconium ions. The hydrogel can realize motion monitoring and transdermal drug delivery functions, and has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a hydrogel for motion monitoring and / or drug delivery and a preparation method and application thereof. Background Art

[0002] Monitoring the human body's motion state is of great significance for health management and personalized medicine. Regular analysis of physical status is helpful for disease prevention and diagnosis. Wearable flexible electronic sensors have the ability to monitor physical indicators such as strain and motion, and can be used in fields such as identity authentication, motion analysis, human-computer interaction, fall detection, and real-time health monitoring. They have been used in intelligent gait recognition systems to detect limb coordination and gait patterns. However, traditional conductive materials face application challenges due to poor flexibility, poor fit, and low biocompatibility. Ideal flexible sensor materials need to have excellent stretchability, high sensitivity, degradability, and self-healing properties to improve device life and expand the scope of application. At the same time, athletes may suffer from muscle strain or joint inflammation due to various reasons such as excessive fatigue or irregular movements, resulting in chronic pain, inflammation, and impaired motor function. In order to solve these problems, it is particularly important to continuously and stably deliver targeted drugs while monitoring the patient's motion state. Transdermal drug delivery systems have the advantages of avoiding first-pass effects, providing stable blood drug concentrations, reducing drug concentration peaks, targeted drug delivery, and improving patient compliance and health outcomes. The ability to deliver drugs for a long time while detecting human motion provides an option for the long-term management of chronic pain diseases in athletes.

[0003] Hydrogels show promise in the fields of tissue scaffolds, tissue adhesives, electronic skin devices, implantable electronic devices, artificial muscles, wearables, medical robots, and drug delivery systems. Hydrogels have excellent electrical conductivity and adjustable mechanical properties, making them ideal materials for flexible sensors. Due to their unique properties such as high water content, high electrical conductivity, low elastic modulus, and high biocompatibility, hydrogel materials have physical, chemical, and mechanical properties similar to those of biological tissues, making them suitable for monitoring physiological signals in the human body. Although lipophilic pressure-sensitive adhesives are widely used in transdermal drug delivery systems, they are more suitable for small-dose administration. They have low drug loading and poor air permeability. In contrast, hydrophilic polymers, such as hydrogels, have good skin affinity and comfort. In summary, hydrogels are good materials for athlete health monitoring and continuous transdermal drug delivery.

[0004] In order to improve the performance of hydrogels, some researchers have proposed that covalent bonds can be introduced through chemical cross-linking to enhance their mechanical properties, but this method may cause problems such as hydrogels being difficult to repair, toxic, and brittle. Summary of the invention

[0005] In view of the above technical problems, the present invention provides a hydrogel for motion detection and / or drug delivery, which can realize motion monitoring and transdermal drug delivery functions and has excellent mechanical properties.

[0006] The present invention provides a hydrogel for motion detection and / or drug delivery, wherein the hydrogel is a double network hydrogel, and the double network hydrogel comprises a first network, a second network, a crosslinker, and a photoinitiator;

[0007] The first network is mainly constructed by N-hydroxyethyl acrylamide-β-(acryloxy) propionic acid copolymer, the second network is mainly constructed by carboxylated cellulose nanofibers, and the crosslinking agent includes zirconium ions.

[0008] In order to overcome the limitations of the above-mentioned introduction of covalent bonds by chemical crosslinking, the inventors propose to introduce reversible dynamic chemical bonds (including the introduction of non-covalent bonds, such as hydrogen bonds, hydrophobic interactions and metal complexes). The dynamic bonds that break under external forces can dissipate a large amount of energy and delay the formation of cracks, thereby improving the toughness of the hydrogel. Among them, the ion coordination toughening strategy is to introduce metal ions into the hydrogel matrix to form coordination bonds with groups such as carboxyl or hydroxyl groups on the polymer chain, and these ions act as physical crosslinking points in the network. At the same time, metal ions can also be used as carriers for electronic conduction. In addition, the double network hydrogel introduces a polymer that can form non-covalent bonds (such as hydrophobic bonds, hydrogen bonds and metal ligand bonds) into the hydrogel network to construct a second network. A stable polymer structure is formed by using a densely crosslinked first network and a loosely crosslinked second network, so the double network hydrogel has higher mechanical strength and toughness. Based on this, the inventors constructed a network with N-hydroxyethyl acrylamide-β-(acryloyloxy) propionic acid copolymer as the first network (P(CEA-Co-NHEAA)), carboxylated cellulose nanofibers (CNF-C) as the second network, and zirconium ions (Zr 4+ ) as a physical crosslinker in double network hydrogels to achieve motion monitoring and transdermal drug delivery functions (e.g. Figure 1 shown).

[0009] In one embodiment, the zirconium ions form a metal coordination complex with the carboxyl and hydroxyl groups of the first network and the carboxyl and hydroxyl groups of the second network.

[0010] Zr 4+ The ions form strong metal coordination complexes with the carboxyl and hydroxyl groups of the polymer, which endows the hydrogel with excellent mechanical properties.

[0011] In one embodiment, the N-hydroxyethyl acrylamide-β-(acryloxy) propionic acid copolymer is prepared from N-hydroxyethyl acrylamide and β-(acryloxy) propionic acid;

[0012] The usage ratio of the crosslinking agent, carboxylated cellulose nanofibers, N-hydroxyethyl acrylamide, β-(acryloxy) propionic acid and photoinitiator is (0.1%-1%): (0.05%-2%): (10%-20%): (15%-30%): (0.05%-0.16%).

[0013] The present invention also provides a method for preparing the hydrogel, comprising the following steps:

[0014] The crosslinking agent and carboxylated cellulose nanofibers are mixed, and N-hydroxyethyl acrylamide, β-(acryloyloxy) propionic acid and a photoinitiator are added and mixed to obtain a hydrogel precursor, and a polymerization reaction is carried out to obtain a hydrogel.

[0015] In one embodiment, the usage ratio of the crosslinking agent, carboxylated cellulose nanofibers, N-hydroxyethyl acrylamide, β-(acryloxy) propionic acid, and photoinitiator is (0.1%-1%): (0.05%-2%): (10%-20%): (15%-30%): (0.05%-0.16%).

[0016] In one embodiment, the cross-linking agent includes ZrCl4.

[0017] In one embodiment, the photoinitiator includes: at least one of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO for short), ethyl 2,4,6-trimethylbenzoylphosphonate (TPO-L for short), 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone (photoinitiator 907 for short), 2-isopropylthioxanthone (ITX for short), 1-hydroxy-cyclohexyl-phenyl ketone (photoinitiator 184 for short), 2-hydroxy-2-methyl-1-phenyl-1-propanone (photoinitiator 1173 for short), and IRGACURE127.

[0018] In one embodiment, the polymerization reaction conditions include: ultraviolet light irradiation.

[0019] In one embodiment, the light irradiation includes: 300-400nm ultraviolet irradiation for 5-10min.

[0020] The present invention also provides application of the hydrogel in a flexible sensor or a transdermal drug delivery system.

[0021] The present invention also provides a flexible sensor which transmits electrical signals through the hydrogel.

[0022] In one of the embodiments, the flexible sensor is a flexible strain sensor.

[0023] The present invention also provides a transdermal drug delivery system, comprising a drug and a carrier, wherein the carrier comprises the hydrogel.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The hydrogel for motion monitoring and / or drug delivery of the present invention, as well as the preparation method and application thereof, can realize the functions of motion monitoring and transdermal drug delivery, and has excellent mechanical properties, with a stretching ratio of up to 1150%, a tensile stress of 0.32 MPa, and a toughness of 1.64±0.26 MJ / m 3 . BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a method for preparing a hydrogel for motion detection and / or drug delivery, and a schematic diagram of the effect, wherein Figure 1 a is a process flow chart of the preparation method, Figure 1 b is a schematic diagram of the hydrogel realizing motion monitoring and transdermal drug delivery functions;

[0027] Figure 2 : is a diagram showing the structural characterization results of the hydrogel in the embodiment, wherein Figure 2 a is the SEM image of the cross section of P(CEA-co-NHEAA) gel, Figure 2 b is the SEM image of the cross section of Ion-P (CEA-co-NHEAA) hydrogel. Figure 2 c is the SEM image of the cross section of Ion-CP (CEA-co-NHEAA) hydrogel. Figure 2 b. Figure 2 c The lower left corner is the energy dispersive X-ray spectrum, Figure 2 d is the Fourier transform infrared spectra of P(CEA-co-NHEAA), Ion-P(CEA-co-NHEAA), and Ion-CP(CEA-co-NHEAA), Figure 2 e is the Raman spectra of P(CEA-co-NHEAA), Ion-P(CEA-co-NHEAA), and Ion-CP(CEA-co-NHEAA), Figure 2 fi is the X-ray photoelectron spectroscopy analysis results of P(CEA-co-NHEAA), Ion-P(CEA-co-NHEAA), and Ion-CP(CEA-co-NHEAA);

[0028] Figure 3 The figure is a result diagram of the mechanical properties characterization of the hydrogel in the embodiment, wherein: Figure 3 a is different Zr 4+ The mechanical properties of the hydrogel at the dosage, Figure 3 b is different Zr4+ The toughness results of the hydrogel at the dosage, Figure 3 c is different Zr 4+ Compression curve of hydrogel at dosage, Figure 3 d is 0.2wt% Zr 4+ The mechanical properties of hydrogels with different CNF-C dosages when the added amount remains unchanged. Figure 3 e is 0.2wt% Zr 4+ The toughness results of hydrogels with different CNF-C dosages when the added amount remains unchanged. Figure 3 f is 0.2wt% Zr 4+ The durability of hydrogels with different CNF-C dosages when the added amount remains unchanged. Figure 3 gi is a schematic diagram showing that Ion-CP (CEA-co-NHEAA) has a wide range of deformation capabilities;

[0029] Figure 4 : is a graph showing the results of the adhesion performance experiment of the hydrogel in the embodiment, wherein Figure 4 a is the adhesion result of Ion-CP (CEA-co-NHEAA), Figure 4 b is the statistical diagram of the bonding strength of Ion-CP (CEA-co-NHEAA) with glass, wood, plastic, aluminum, and copper, respectively. Figure 4 c is the operation diagram of the adhesion performance experiment. Figure 4 d is the schematic diagram of the bonding experiment of Ion-CP (CEA-co-NHEAA) with glass, wood, plastic, aluminum, and copper, respectively. Figure 4 e is a diagram illustrating the principle of achieving better bonding between different functional groups in Ion-CP (CEA-co-NHEAA) and different materials. Figure 4 f is a schematic diagram of the self-healing efficacy of the Ion-CP (CEA-co-NHEAA) dual network;

[0030] Figure 5 The sensor performance experimental results in the embodiment are shown in FIG. Figure 5 a is different Zr 4+ The ionic conductivity results of the hydrogel at the dosage are shown in the figure. Figure 5 b is the sensitivity factor (GF) result diagram of Ion-CP (CEA-co-NHEAA) double network hydrogel sensor. Figure 5 c. Figure 5 d is the result of the electromechanical test experiment of Ion-CP (CEA-co-NHEAA), Figure 5 e is the result of the stable resistance response of the Ion-CP (CEA-co-NHEAA) hydrogel sensor at various stretching rates. Figure 5f is the step response signal result diagram of Ion-CP (CEA-co-NHEAA) hydrogel sensor under gradient stretching and relaxation. Figure 5 g is the response and recovery time result diagram of Ion-CP (CEA-co-NHEAA) hydrogel sensor under 50% strain. Figure 5 h is the result of 500 continuous long-term cycle tests of the Ion-CP (CEA-co-NHEAA) hydrogel sensor;

[0031] Figure 6 The figure is a human motion monitoring experimental result diagram of the Ion-CP (CEA-co-NHEAA) double network hydrogel in the embodiment, wherein: Figure 6 af are the electrical signal results of six different parts (shoulder, cheek, neck, wrist, finger, knee) under motion state, Figure 6 g is the result graph of motion signals of the same part with different frequencies;

[0032] Figure 7 The results of the transdermal administration experiment in the embodiment are shown in FIG. Figure 7 a is a schematic diagram of the experimental setup. Figure 7 b is the release curves of three hydrogels: P (CEA-co-NHEAA), Ion-P (CEA-co-NHEAA) and Ion-CP (CEA-co-NHEAA) within 24 hours. Figure 7 The curves in b are P(CEA-co-NHEAA), Ion-CP(CEA-co-NHEAA), and Ion-P(CEA-co-NHEAA) from top to bottom. Figure 7 c is the skin permeation of three hydrogels, P (CEA-co-NHEAA), Ion-P (CEA-co-NHEAA) and Ion-CP (CEA-co-NHEAA) within 24 h. Figure 7 The curves in c are P(CEA-co-NHEAA), Ion-CP(CEA-co-NHEAA), and Ion-P(CEA-co-NHEAA) from top to bottom. Figure 7 dg is the result of the biosafety evaluation of the Ion-CP (CEA-co-NHEAA) hydrogel patch, Hydrogel is Ion-CP (CEA-co-NHEAA), Positive is 10% sodium dodecyl sulfate SDS solution, Figure 7 The horizontal axis of f from left to right is Blank, Hydrogel, and Positive. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0035] source:

[0036] Unless otherwise specified, the reagents, materials, and equipment used in this example are all commercially available; the experimental methods are all conventional experimental methods in the art unless otherwise specified.

[0037] Example

[0038] 1. Preparation of hydrogel.

[0039] The hydrogel was prepared by a simple one-pot method. First, ZrCl4 and carboxylated cellulose nanofibers were added to a glass sample bottle and stirred with water. Then, N-hydroxyethyl acrylamide (CEA) monomer and β-(acryloyloxy) propionic acid (NHEAA) monomer were added to the above solution and mixed thoroughly. Next, the hydrogel precursor solution was pipetted into a polytetrafluoroethylene mold. Finally, the mold was placed in a 365nm ultraviolet irradiation environment for 5 minutes to complete the polymerization and obtain a hydrogel (Ion-CP (CEA-co-NHEAA)). The dosage ratio of ZrCl4, carboxylated cellulose nanofibers, N-hydroxyethyl acrylamide (CEA) monomer and β-(acryloyloxy) propionic acid (NHEAA) monomer was (0.1%-1%): (0.05%-2%): (10%-20%): (15%-30%).

[0040] That is, the hydrogel is prepared from the following raw materials in percentage by mass:

[0041]

[0042] 2. Structural characterization results.

[0043] The hydrogels containing only N-hydroxyethyl acrylamide (CEA) monomer and β-(acryloyloxy) propionic acid (NHEAA) monomer were synthesized by one-pot method, and the metal ion Zr 4+ hydrogel, and the addition of metal ions Zr 4+The hydrogels of CEA-co-NHEAA, Ion-P (CEA-co-NHEAA), and Ion-CP (CEA-co-NHEAA) were named respectively and characterized.

[0044] 1. First, in order to intuitively display Zr 4+ The effects of ions and CNF-C on the micromorphology of hydrogels were investigated by scanning electron microscopy images of P(CEA-co-NHEAA), Ion-P(CEA-co-NHEAA), and Ion-CP(CEA-co-NHEAA).

[0045] like Figure 2 As shown in a, the SEM image of the cross section of the P(CEA-co-NHEAA) gel shows a disordered and loose porous structure. 4+ ions and CNF-C, as Figure 2 As shown in c, the cross-section of Ion-CP (CEA-co-NHEAA) hydrogel presents an ordered and interconnected honeycomb porous structure. These porous structures provide more channels for the rapid transport of ions, which is conducive to the rapid transport of Zr 4+ The results of energy dispersive X-ray spectroscopy are presented in Figure 2 b and Figure 2 In the lower left corner of c, the results show that the Zr element is evenly distributed in the hydrogel skeleton, ensuring the transmission of conductive substances and metal ions.

[0046] 2. Excellent mechanical properties of double network hydrogel and Zr 4+ The strong metal coordination bonds between ions and carboxyl groups in the network and the Zr 4+ ions and the coordination bonds formed by the hydroxyl groups in the network. This inference was confirmed by Fourier transform infrared spectroscopy ( Figure 2 d).

[0047] In the infrared spectrum of P(CEA-co-NHEAA), 1413.16 cm -1 The infrared peak is attributed to COO - The stretching vibration peak of Zr 4+ The ions of Ion-P (CEA-co-NHEAA) and Ion-CP (CEA-co-NHEAA) were blue-shifted to 1443.16 cm-1 and 1443.16 cm-1, respectively. -1 and 1442.58cm -1 The Raman spectrum also confirmed that the carboxylic acid-Zr 4+ The formation of complexes ( Figure 2 e). With Zr-free 4+Compared with the P(CEA-co-NHEAA) gel with ions, Zr 4+ COO of ion-toughened Ion-P (CEA-co-NHEAA) and Ion-CP (CEA-co-NHEAA) hydrogels - The two characteristic peaks of the group are 1450.64cm -1 and 1723.75cm -1 Transfer to 1451.55cm -1 and 1728.95cm -1 、1452.45cm -1 and 1728.08cm -1 .

[0048] In addition, the infrared spectrum of P(CEA-co-NHEAA) at 3346.91 cm -1 The peak is attributed to the stretching vibration of hydroxyl groups. 4+ The red shifts to 3298.91 cm in Ion-P (CEA-co-NHEAA) and Ion-CP (CEA-co-NHEAA) of ions were -1 and 3300.08cm -1 , which also indicates the formation of a coordination bond.

[0049] 3. In order to further explore the relationship between carboxyl groups and Zr in the hydrogel network 4+ The coordination effect of ions was analyzed by X-ray photoelectron spectroscopy (X-ray photoelectron spectroscopy) of P(CEA-co-NHEAA), Ion-P(CEA-co-NHEAA) and Ion-CP(CEA-co-NHEAA). Figure 2 fi). Figure 2 As shown in h, the O1s graph of Ion-CP (CEA-co-NHEAA) has three peaks, of which the binding energies of the two peaks are 530.8 eV and 533.4 eV, representing CO and C=O respectively. 4+ A peak with a binding energy of 532 eV, which was not seen in the pure monomer gel, appeared in the ion-toughened Ion-P (CEA-co-NHEAA) and Ion-CP (CEA-co-NHEAA), representing the CO-Zr bond, indicating the formation of carboxyl-Zr 4+ By fitting the Zr3d peak in Ion-CP(CEA-co-NHEAA), two peaks with binding energies of 182.8 eV and 185.3 eV were obtained, corresponding to Zr 3d 5 / 2 and Zr3d 3 / 2 .like Figure 2 As shown in (f), the P(CEA-co-NHEAA) hydrogel synthesized from pure monomers does not contain the Zr element.

[0050] 3. Mechanical properties characterization results.

[0051] 1. Adding different types of metal ions into the hydrogel double network structure, it is found that Zr 4+ The mechanical properties of the hydrogels are greater than those containing Fe 3+ >Ca 2+ >Mg 2+ >Li + .

[0052] Table 1 Effects of different metal ions on mechanical properties and electrical conductivity

[0053] project Tensile strain% Stress MPa Conductivity mS / cm <![CDATA[Zr-containing 4+ hydrogel]]> 1154 0.32 1.43 <![CDATA[Containing Fe 3+ hydrogel]]> 902 0.30 1.32 <![CDATA[Calcium-containing 2+ hydrogel]]> 980 0.27 1.23 <![CDATA[Mg-containing 2+ hydrogel]]> 900 0.25 1.29 <![CDATA[Li-containing + hydrogel]]> 860 0.22 1.21

[0054] 2. In order to study Zr 4+ and CNF-C on the hydrogel system, and the mechanical properties of all samples were evaluated.

[0055] Table 2Zr 4+ The screening formula composition table of the amount

[0056] Sample name CEA(g) NHEAA(g) <![CDATA[ZrCl2(g)]]> TPO(g) <![CDATA[H2O(mL)]]> <![CDATA[0.2wt%Zr 4+ Hydrogel]]> 2 3 0.066 0.01 8 <![CDATA[0.3wt%Zr 4+ Hydrogel]]> 2 3 0.1 0.01 8 <![CDATA[0.4wt%Zr 4+ Hydrogel]]> 2 3 0.133 0.01 8 <![CDATA[0.5wt%Zr 4+ Hydrogel]]> 2 3 0.166 0.01 8

[0057] Table 3 Screening formula composition of CNF-C

[0058]

[0059] like Figure 3 As shown in a, with the Zr 4+ With the increase of Zr content, the strain of Ion-P(CEA-co-NHEAA) hydrogel decreases continuously (the screening formula is shown in Table 2). 4+ The ions were over-crosslinked with the functional groups (such as carboxyl and hydroxyl) in the hydrogel, resulting in a stronger physical crosslinking effect, causing the structure of the hydrogel to become denser. 4+ When the ion addition amount is 0.2wt%, the maximum tensile strain at the fracture of the hydrogel reaches 749% and the maximum stress is 0.1MPa. 4+ The toughness of the ionic hydrogel is about 0.27±0.04MJ m - 3( Figure 3 b). Figure 3 c is the compression curve of the hydrogel. 4+ When the ion content is 0.8wt%, the compressive strength of Ion-P(CEA-co-NHEAA) reaches 1.6MPa. 4+When the ion content continued to increase to 1wt%, the compressive strength of Ion-P(CEA-co-NHEAA) did not continue to increase significantly. 4+ The increase in the amount of ions added further explains that Zr 4+ The ions produce coordination bonds with the polymer, resulting in a denser hydrogel structure.

[0060] Keep 0.2wt% Zr 4+ The effect of CNF-C on the mechanical properties of hydrogels was investigated with the addition amount unchanged. Figure 3 d, the addition of CNF-C greatly improved the mechanical properties of the hydrogel (the screening formula is shown in Table 3). When 0.5wt% CNF-C was added, the maximum tensile strain at break increased to 1154%, and the maximum stress increased to 0.32MPa. Correspondingly, the toughness of Ion-CP (CEA-co-NHEAA) hydrogel was about 607% higher than that of Ion-P (CEA-co-NHEAA) hydrogel (1.64±0.26kJ m - 3)( Figure 3 e). Cycling tests were performed to evaluate the durability of Ion-CP(CEA-co-NHEAA) hydrogels ( Figure 3 f). The results show that at small strains (10% to 50%), the strain curve of the sample overlaps with the release curve, showing a linear reversible characteristic. When the strain is 100% to 300%, there is a small hysteresis curve between the strain and the release curve, which may be related to the destruction of non-covalent interactions in the hydrogel network leading to energy dissipation, but the process is reversible. After the Ion-CP (CEA-co-NHEAA) hydrogel recovers for a period of time, the sensor can still return to the initial mechanical level. The Ion-CP (CEA-co-NHEAA) hydrogel can also return to the initial mechanical level after a period of recovery.

[0061] Ion-CP(CEA-co-NHEAA) hydrogels have a wide range of deformability and can be stretched ( Figure 3 g), distortion ( Figure 3 h); Even if pierced by a sharp object, they can remain intact and quickly return to their original shape ( Figure 3 i). This observation emphasizes the excellent mechanical recovery properties of the hydrogel.

[0062] The 0.5wt% CNF-C hydrogel in Table 3 was selected for subsequent adhesion and sensing experiments. The dosage ratio (mass percentage ratio) of the crosslinker, carboxylated cellulose nanofibers, N-hydroxyethyl acrylamide, β-(acryloyloxy) propionic acid, and photoinitiator in the hydrogel was 0.5%: 0.5%: 15.22%: 22.83%: 0.08%, and the balance was water.

[0063] 3. Adhesion performance experiment.

[0064] Due to the excellent adhesion properties of Ion-CP (CEA-co-NHEAA) double network hydrogel, close adhesion between the gel sensor and the substrate can be achieved without adding adhesives.

[0065] In order to verify its adhesion performance, an adhesion separation experiment was conducted to study the adhesion performance of Ion-CP (CEA-co-NHEAA) dual network hydrogel. The lap shear test (ASTM F2255) was adopted to gradually separate the substrates bonded by the hydrogel using a universal material testing machine, and the adhesion force ( Figure 4 a). Various organic and inorganic materials are used as substrates, including glass, wood, plastic, aluminum, copper.

[0066] The results are as follows Figure 4 a and Figure 4 As shown in b, the hydrogel has the best adhesion to glass, with an adhesion force of 14 N. The bonding strength is obtained by calculating the maximum adhesion force divided by the overlapping contact area, as shown in Figure 4 As shown in (b), the bonding strengths of glass, wood, plastic, aluminum, and copper are 65.06±4.67 kPa, 46.90±8.75 kPa, 26.73±4.31 kPa, 19.59±1.57 kPa, and 8.28±2.64 kPa, respectively. These adhesion properties between the Ion-CP (CEA-co-NHEAA) double network hydrogel and the substrate are mainly derived from the multiple hydrogen bonds of the hydrogel.

[0067] At the same time, there are no residual impurities on the surface of the substrate of Ion-CP (CEA-co-NHEAA) double network hydrogel during the peeling process, and its excellent adhesion ensures the feasibility of application on human skin, robotic arms or intelligent robots. In addition, Ion-CP (CEA-co-NHEAA) double network hydrogel has many reversible non-covalent bonds in its network, including metal coordination bonds, hydrogen bonds, etc., which give it the ability to self-heal. Figure 4 f shows the self-healing ability of the Ion-CP (CEA-co-NHEAA) double network, and it can still conduct electricity after self-healing. The self-healing ability ensures that the hydrogel has a certain self-repair ability after being damaged.

[0068] 4. Sensing performance experiment.

[0069] Zr 4+ The introduction of ions makes the hydrogel exhibit excellent electrical conductivity and can be regarded as a stretchable conductor, such as Figure 5 a, 0.2wt% Zr 4+ The ionic conductivity of the hydrogel is 1.43 mS / cm, which is higher than that of other ions (as shown in Table 1). 4+ As the amount of Zr added increases, the ionic conductivity of the hydrogel increases first and then decreases. This phenomenon may be related to the 4+ The ion accumulation effect is related to the excessive Zr 4+ Ions may form precipitation or condensation, which hinders the uniform distribution and migration of ions. At the same time, the interaction between ions is enhanced (such as electrostatic effect), resulting in a decrease in ion migration ability. However, the overall difference is not large, which meets the conductivity requirements of the sensor.

[0070] Sensitivity factor (GF) is another key parameter for evaluating the sensing performance of sensors. Figure 5 As shown in (b), the GF value of the Ion-CP (CEA-co-NHEAA) dual network hydrogel sensor presents three different linear regions: in the 0-500% strain range, the GF is 0.236; in the 500-850% strain range, the GF is 0.376; in the 850-1100% strain range, the GF is as high as 1.241. This sensitivity can meet the current mainstream sensitivity of the daily needs of gel-based strain sensors.

[0071] To further evaluate the performance of the sensor, a series of electromechanical tests were performed. Figure 5 c and Figure 5 As shown in Figure d, the Ion-CP (CEA-co-NHEAA) dual network hydrogel sensor exhibits a stable and reversible response over a wide strain range, and the sensor can reliably detect small strains as low as 0.1% with high reproducibility. Figure 5 As shown in e, the hydrogel sensor maintains a stable resistance response at various stretching rates. When subjected to gradient stretching, the sensor generates a step response signal and can return to its original state when relaxed ( Figure 5 f). At 50% strain, the response and recovery times of the sensor are 36 ms and 53 ms, respectively ( Figure 5 g). In addition, the fluctuation of the sensor resistance response signal remained highly stable during 500 consecutive long-term cycle tests, showing excellent stability ( Figure 5 h). These studies demonstrated that the Ion-CP(CEA-co-NHEAA) dual-network hydrogel sensor possesses sensitive, accurate, and stable deformation monitoring capabilities.

[0072] 5. Human motion monitoring.

[0073] The above experimental data show that Ion-CP (CEA-co-NHEAA) double network hydrogel has comprehensive properties such as flexibility, stretchability, self-adhesion, self-healing and high sensitivity, and has the potential to be used as a flexible strain sensor to monitor large-scale and subtle body movements.

[0074] To demonstrate this, the inventors used a hydrogel sheet of Ion-CP (CEA-co-NHEAA) attached to the skin as a sensor to monitor the motion status of six different parts (shoulder, cheek, neck, wrist, finger, knee) Figure 6 af). Different joint movements can cause different degrees of deformation of the hydrogel attached to the skin, thereby generating electrical signals of different sizes. When attached to the shoulders, wrists, and neck, timely and stable electrical signals can be monitored. In addition, Ion-CP (CEA-co-NHEAA) hydrogel can monitor large-strain stable signals such as knee bending, as well as small-strain signals such as 30° finger bending, and can distinguish different angles of finger bending. At the same time, motion signals of different frequencies can also be monitored. When the hydrogel is attached to the knee, different but stable electrical signals can be generated when walking, jogging, and sprinting. ( Figure 6 g). The above experimental results show that the Ion-CP (CEA-co-NHEAA) double network hydrogel has high sensitivity and can be used as a flexible strain sensor to monitor human body movements of different sizes and frequencies in a timely and stable manner.

[0075] 6. Application of hydrogels in transdermal drug delivery systems.

[0076] The above experimental results show that Ion-CP (CEA-co-NHEAA) double network hydrogel has excellent mechanical properties and adhesion properties, and has the potential to be used in transdermal drug delivery systems. Therefore, flurbiprofen was loaded into the double network hydrogel as a model drug, and in vitro release experiments and transdermal permeation experiments were carried out to investigate its transdermal drug delivery performance. The experimental device is as follows: Figure 7 As shown in a.

[0077] The release profiles of the three hydrogels within 24 h were shown in Figure 7 b. At 24 h, the cumulative release amounts of the three hydrogels were 487.71 ± 40.46 μg / cm 2 , 426.08±31.89μg / cm 2 , 409.70±34.27μg / cm 2It is worth noting that the drug release behavior of the double network hydrogel Ion-CP (CEA-co-NHEAA) satisfies the zero-order release, that is, the release rate remains constant during the drug release to achieve controlled release; while the pure monomer P (CEA-co-NHEAA) hydrogel shows a release characteristic similar to that of traditional hydrogels: the release rate gradually slows down. In the double network hydrogel Ion-CP (CEA-co-NHEAA), the network formed by metal coordination bonds and hydrogen bonds controls the drug release at a constant rate, thereby weakening the effect of concentration gradient on the drug release rate. Figure 7 c shows the skin permeation of the three hydrogels P (CEA-co-NHEAA), Ion-P (CEA-co-NHEAA) and Ion-CP (CEA-co-NHEAA) within 24 hours. At 24 hours, the cumulative permeation of the three hydrogels was 299.18 ± 103.36 μg / cm 2 , 257.70±38.13μg / cm 2 , 287.22±37.28μg / cm 2 It can be seen that Ion-CP (CEA-co-NHEAA) can maintain a constant rate of permeation, further verifying its potential for application in sustained-release transdermal drug delivery.

[0078] Biosafety evaluation results such as Figure 7 As shown in dg, the Ion-CP (CEA-co-NHEAA) hydrogel patch did not cause any irritation to the skin. After in vivo skin irritation experiments and histological analysis, it was found that 24 hours after the application of the hydrogel patch, no skin irritation, edema or cytotoxicity occurred in the test area, and the ΔEI value of the Ion-CP (CEA-co-NHEAA) hydrogel group was not significantly different from that of the blank group (p>0.05). In contrast, the positive control group (using 10% sodium dodecyl sulfate SDS solution) caused severe skin damage, including thickening and pigmentation, and the ΔEI value increased significantly (p<0.05), indicating that the skin was strongly stimulated. The results of H&E staining further confirmed that the SDS solution caused acute irritation, while the Ion-CP (CEA-co-NHEAA) hydrogel did not cause inflammatory cell recruitment or histopathological changes.

[0079] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0080] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A hydrogel for motion monitoring and / or drug delivery, characterized in that The hydrogel is a double network hydrogel, which comprises a first network, a second network, a crosslinking agent, and a photoinitiator; The first network is mainly constructed by N-hydroxyethyl acrylamide-β-(acryloxy) propionic acid copolymer, the second network is mainly constructed by carboxylated cellulose nanofibers, and the crosslinking agent includes zirconium ions.

2. The hydrogel according to claim 1, characterized in that The zirconium ions form a metal coordination complex with the carboxyl and hydroxyl groups of the first network and the carboxyl and hydroxyl groups of the second network.

3. The hydrogel according to claim 1, characterized in that The N-hydroxyethyl acrylamide-β-(acryloxy) propionic acid copolymer is prepared from N-hydroxyethyl acrylamide and β-(acryloxy) propionic acid; The usage ratio of the crosslinking agent, carboxylated cellulose nanofibers, N-hydroxyethyl acrylamide, β-(acryloxy) propionic acid and photoinitiator is (0.1%-1%): (0.05%-2%): (10%-20%): (15%-30%): (0.05%-0.16%).

4. The method for preparing the hydrogel according to any one of claims 1 to 3, characterized in that: The following steps are involved: The crosslinking agent and carboxylated cellulose nanofibers are mixed, and N-hydroxyethyl acrylamide, β-(acryloyloxy) propionic acid and a photoinitiator are added and mixed to obtain a hydrogel precursor, and a polymerization reaction is carried out to obtain a hydrogel.

5. The preparation method according to claim 4, characterized in that: The usage ratio of the crosslinking agent, carboxylated cellulose nanofibers, N-hydroxyethyl acrylamide, β-(acryloxy) propionic acid and photoinitiator is (0.1%-1%): (0.05%-2%): (10%-20%): (15%-30%): (0.05%-0.16%).

6. The preparation method according to claim 4, characterized in that: The crosslinking agent includes ZrCl4.

7. The preparation method according to claim 4, characterized in that: The polymerization reaction conditions include: ultraviolet light irradiation.

8. Use of the hydrogel according to any one of claims 1 to 3 in a flexible sensor or a transdermal drug delivery system.

9. A flexible sensor, characterized in that: The electrical signal is transmitted through the hydrogel according to any one of claims 1 to 3.

10. A transdermal drug delivery system, characterized in that: The invention comprises a drug and a carrier, wherein the carrier comprises the hydrogel according to any one of claims 1 to 3.

Citation Information

Cited By

  • Dynamic hydrogen bond enhanced double-layer hydrogel and interface toughening preparation method thereof

    CN120552425A

  • A dynamic hydrogen bond enhanced double-layer hydrogel and an interfacial toughening preparation method thereof

    CN120552425B